PERANCANGAN PENATAAN KAWASAN KAMPUS II UIN ALAUDDIN DI SAMATA KABUPATEN GOWA - Zulkarnain AS; Faris Jumawan; Muh. Rante Manga (Teknosains, 2017)
As one of the major campuses in the region Mamminasata,UIN Alauddin showed a very significant improvement. Since movinginto second campus located in Samata Gowa in 2010, Alauddin StateIslamic University is growing from day to day. Starting from thedevelopment of lecturers, employees, increasing the number ofstudents to the fulfillment of the facility, as well as the improvement ofthe environment in the campus area. But in an effort to meet the needsof the facility and the environmental improvements there beberpaobstacles that must be faced. The increasing need some academicfacilities, institutional, and environmental concomitant increase in thenumber of lecturers, employees and the number of students. Thus it isnecessary to design the arrangement of the campus area inanticipation of a surge in the need of parking, classrooms andadministration, sports facilities and places of worship, as well as theneed for open green space. Structuring is done in the form ofrelocation and renovation as well as the addition of some constructionof new facilities by utilizing the potential locations are in areas of thecampus.